A study of grafting reactions during processing of polyolefins - Machado, A. V. (2004)
The effects of polyolefins composition, that is polyethylene (PE), polypropylene (PP) and a ethylene/propylene copolymer (EPM) of 45/55 monomer ratio, and of operating conditions (screw speed, throughput and screw configuration) on the grafting of maleic anhydride (MA) were investigated. Sampling devices located along the extruder barrel were used to collect samples of modified PE, EPM, and PP that were subsequently characterized in order to monitor the degree of grafting and of crosslinking/degradation. Although a similar trend of MA grafting evolution is observed along the extruder, the final MA graft content depends on the processing parameters, screw configuration, and particularly, throughput have a significant effect on the grafting yield. Taking PE as an example, and by means of a statistical experimental design, an optimal operating window in terms of screw speed, throughput, and geometry was identified, yielding MA graft contents of 2 wt% MA.